Modelling and simulation of structural, electronic and optical properties of organic semiconducting materials - Mohamad, Mazmira (2017)
Organic semiconductor materials (OSMs) involving thiophene, vinazene, di-indenoperylene (DIP) and copper phthalocyanine (CuPc) are computationally explored at both the isolated molecule and the molecular crystal levels, to expose their potential in optoelectronics. The calculations are performed within the first-principles pseudo-potential quantum mechanical approaches designed within density functional theory at the level of different flavors of exchange-correlation energy/potential functional. All the studied molecules exhibit π-orbital and free electron pairs. The study revealed that the total energy values of isolated molecules of thiophene, vinazene, di-indenoperylene (DIP) and CuPc are 552.7140Ha, 487.7079Ha, 1227.9865Ha and 1887.9308Ha respectively, and those for the corresponding molecular crystals are 5337.5117Ha, 3901.8748Ha, 2455.2992Ha and 3775.2523Ha respectively. In the electronic structure investigations, it is found that the delocalization of electrons from the π-conjugation characteristics of the OSMs, has resulted in the electronic hybridization in their electronic structures, and consequently, increased the charge population in the highest occupied molecular orbitals. The obtained energy-gap values for CuPc, DIP, vinazene and thiophene molecules are 0.847eV, 1.490eV, 3.300eV and 4.723eV respectively. In investigations of the optical properties, substantially high values of absorption observed particularly in molecular crystals, accompanied with low values of resistivity, have resulted in the significant lowering of the loss function. The moderate charge carrier mobility in OSMs is also reflected from the obtained dielectric function and conductivity spectra. Besides, on the application part, the graphene zero energy-gap is resolved via the study of thiophene molecule as the adsorbate and graphene surface as the substrate by employing the interfacial approach. To validate the OSM findings for organic photovoltaic (OPV) applications, performance calculations of a simulated vinazene-based device have been executed. From the obtained results that show peak shifting in transmission spectra, gradual increasing of current in current-voltage (I-V) characteristic curve and conductance spectra that exhibit a sinusoidal pattern, it is believed that vinazene molecule can be recognized as good OPV active material.